Ethyl beta-carboline carboxylate lowers seizure threshold and antagonizes flurazepam-induced sedation in rats. - Cowen, P; Green, A; Nutt, D (1981)
The mammalian central nervous system possesses specific high-affinity binding sites for the benzodiazepines and considerable evidence suggests that these binding sites are the pharmacological receptors through which these compounds act. Recently, ethyl beta-carboline-3-carboxylate (beta-CCE) has been identified in both human urine and rat brain. beta-CCE may be closely related to the endogenous ligand for the benzodiazepine receptor--it shows an affinity for the receptor of the same order as that of clonazepam, one of the most potent benzodiazepines, and is the first non-diazepinoid structure to be identified with an affinity in the nanomolar range. Furthermore, it is selective for the benzodiazepine receptor. Clinically and in animal studies, benzodiazepines have anti-convulsant, hypnotic and anxiolytic actions. We have therefore investigated whether beta-CCE exhibits any of these properties in rats. We report here that, in contrast to the benzodiazepines, beta-CCE lowers seizure threshold and reverses the sedative effect of flurazepam. If beta-CCE has a close structural relationship to the endogenous ligand, benzodiazepines may be antagonistic at the receptor site.